The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1016/s0022-5347(17)41805-2
|View full text |Cite
|
Sign up to set email alerts
|

Transrectal Ultrasonography in the Diagnosis and Staging of Carcinoma of the Prostate

Abstract: Transrectal prostatic ultrasonography is a potentially valuable means to evaluate the prostate of men with suspected carcinoma. We studied 118 patients with this modality before histological evaluation of the prostate (20 underwent radical prostatectomy, 75 core needle biopsy and aspiration cytology, and 23 transurethral resection of the prostate). Transrectal ultrasonography was more efficient than digital rectal examination in the staging of carcinoma of the prostate before radical prostatectomy. The value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
5

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(12 citation statements)
references
References 11 publications
0
6
1
5
Order By: Relevance
“…This good sensitivity which is found in our study and in the literature is unfortunately counterbalanced by the different échographie patterns of prostatic carcinoma [ 1,6,13,14]. Malignant areas may appear hypoechoic, isoechoic or hyperechoic in relation with their volumes and their pathological aspects.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…This good sensitivity which is found in our study and in the literature is unfortunately counterbalanced by the different échographie patterns of prostatic carcinoma [ 1,6,13,14]. Malignant areas may appear hypoechoic, isoechoic or hyperechoic in relation with their volumes and their pathological aspects.…”
Section: Discussioncontrasting
confidence: 42%
“…In the literature the results from transrectal ultrasonography in preoperative staging vary as much as those concerning the diagnosis. The evaluation of the extracapsular extension of the tumor by sonography is better than by digital rectal examination, especially con cerning the seminal vesicles [1,13,14,18,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRUS was twice as sensitive as digital rectal examination in detecting prostate cancer (2.6% vs. 1.3%). 14 The predictive value of a sonographic scan positive for malignancy was 37% in 118 patients examined by Andriole et al 3 Areas of mixed echogenicity and hypoechoic areas are pathognomonic of a prostatic malignancy, but only 984 Acta Cytologica 25 Rosenberg et al detected only one patient with pathologically confirmed stage A cancer of the prostate in 2,214 men. 22 In order to confirm whether FNAB is a reliable method of detecting stage A prostate carcinoma preoperatively, Agatstein et al 1 carried out transrectal FNA biopsy on 120 patients with prostate hyperplasia before undertaking a transurethral resection to confirm their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Patients undergoing a radical prostatec tomy for a T2 cancer are postoperatively upgraded to a T3 lesion based on the ultimate surgical specimen in about 70%. Clinical overstaging of T3 tumors has been reported in 24-50% [35,36], In none of the studies comparing preoperative TRUS with the results obtained by histological examination of the radical prostatectomy specimen, exact tumor volume obtained by TRUS was reported [37][38][39]. It might therefore be worth while, as stated by McNeal et al [40], to include tumor volume as a prognostic factor.…”
Section: Stagingmentioning
confidence: 99%